Biopolymeric Prodrug Systems as Potential Antineoplastic Therapy - Adriana Aurelia Chis; Anca Maria Arseniu; Claudiu Morgovan; Carmen Maximiliana Dobrea; Adina Frum; Anca Maria Juncan; Anca Butuca; Steliana Ghibu; Felicia Gabriela Gligor; Luca Liviu Rus (MDPI AG, 2022)
Nowadays, cancer represents a major public health issue, a substantial economic issue, and a burden for society. Limited by numerous disadvantages, conventional chemotherapy is being replaced by new strategies targeting tumor cells. In this context, therapies based on biopolymer prodrug systems represent a promising alternative for improving the pharmacokinetic and pharmacologic properties of drugs and reducing their toxicity. The polymer-directed enzyme prodrug therapy is based on tumor cell targeting and release of the drug using polymer-drug and polymer-enzyme conjugates. In addition, current trends are oriented towards natural sources. They are biocompatible, biodegradable, and represent a valuable and renewable source. Therefore, numerous antitumor molecules have been conjugated with natural polymers. The present manuscript highlights the latest research focused on polymer-drug conjugates containing natural polymers such as chitosan, hyaluronic acid, dextran, pullulan, silk fibroin, heparin, and polysaccharides from Auricularia auricula.